2020
DOI: 10.2147/cmar.s224791
|View full text |Cite
|
Sign up to set email alerts
|

<p>Managing Ipilimumab-Induced Hypophysitis: Challenges and Current Therapeutic Strategies</p>

Abstract: Over the past years, progress has been made in cancer immunotherapy following the development of immune checkpoint inhibitors (ICI) that have been proved effective in the management of many malignancies. Ipilimumab, a monoclonal antibody against cytotoxic T-lymphocyte antigen-4 (CTLA-4), has been approved for the treatment of advanced melanoma but has been associated with the development of several endocrine immunerelated adverse events (irAEs). Hypophysitis is the most common endocrine irAE related to ipilimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 79 publications
(159 reference statements)
0
21
0
Order By: Relevance
“…Three hundred and twenty-five, 728, 616, and 80 articles were retrieved from the PubMed/Medline, Embase, Web of Science and Cochrane Library databases, respectively, and 8 additional articles were identified from the reference lists of the retrieved articles (7)(8)(9)(10)(11)(12)(13)(14). Ultimately, a total of 114 articles (comprising 206 patients with ICI-induced AI) were included in the study (see Figure 1).…”
Section: The Selection Of Articlesmentioning
confidence: 99%
“…Three hundred and twenty-five, 728, 616, and 80 articles were retrieved from the PubMed/Medline, Embase, Web of Science and Cochrane Library databases, respectively, and 8 additional articles were identified from the reference lists of the retrieved articles (7)(8)(9)(10)(11)(12)(13)(14). Ultimately, a total of 114 articles (comprising 206 patients with ICI-induced AI) were included in the study (see Figure 1).…”
Section: The Selection Of Articlesmentioning
confidence: 99%
“…A systematic review reported that the incidences of pituitary disorders induced by anti-CTLA-4, anti-PD-1, and the combination of anti-CTLA4/anti-PD-1 antibodies were 3.2%, 0.4%, and 6.4%, respectively ( 3 ). It is also known that ipilimumab causes multiple anterior pituitary hormone disorders due to hypophysitis ( 9 ). In addition, while both nivolumab and ipilimumab can induce isolated ACTH deficiency ( 8 ), nivolumab more often causes isolated ACTH deficiency ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic findings seen on the MRI brain are hypo-enhancing lesions in the anterior lobe of the pituitary gland suggesting fibrosis of the gland [ 10 ]. Depending on the severity of the patient's symptoms, the management includes initiation of corticosteroid therapy, hormone replacement therapy to prevent patients from going into adrenal crisis, and sometimes even discontinuation of the offending agent either temporarily or permanently [ 11 ].…”
Section: Discussionmentioning
confidence: 99%